2023
DOI: 10.2147/jir.s412860
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Corrected Anion Gap and the Risk of in-Hospital Mortality in Patients with Acute Pancreatitis: A Retrospective Cohort Study

Abstract: Purpose To explore the prognostic value of albumin corrected anion gap (ACAG) within 24 hours of admission to the intensive care unit (ICU) for acute pancreatitis (AP). Patients and Methods This was a retrospective cohort study. Adult AP patients admitted to ICU from June 2016 to December 2019 were included in the study, who were divided into three groups according to initial serum ACAG within 24 hours upon ICU admission: ACAG ≤ 14.87 mmol/L, 14.87 < ACAG ≤ 19.03 mmol/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…We demonstrated in this study that ACAG has a better predictive value than AG in the prognostic prediction of S-AKI, which implies that ACAG may be an excellent alternative variable in constructing a scoring system. Meanwhile, the advantage of ACAG over AG may not be an isolated case, but may also be a pattern in other diseases (some studies have already confirmed this, including sepsis [ 20 ], acute pancreatitis [ 21 ], and acute myocardial infarction [ 22 ]), and our study provides more evidence for subsequent studies. Furthermore, this advantage of ACAG over AG has some value in the clinic, and perhaps, in the future, ACAG could be a direct substitute for AG in certain diseases.…”
Section: Discussionsupporting
confidence: 56%
“…We demonstrated in this study that ACAG has a better predictive value than AG in the prognostic prediction of S-AKI, which implies that ACAG may be an excellent alternative variable in constructing a scoring system. Meanwhile, the advantage of ACAG over AG may not be an isolated case, but may also be a pattern in other diseases (some studies have already confirmed this, including sepsis [ 20 ], acute pancreatitis [ 21 ], and acute myocardial infarction [ 22 ]), and our study provides more evidence for subsequent studies. Furthermore, this advantage of ACAG over AG has some value in the clinic, and perhaps, in the future, ACAG could be a direct substitute for AG in certain diseases.…”
Section: Discussionsupporting
confidence: 56%
“…16 Li et al conducted a study on 344 patients with acute pancreatitis and found that higher ACAG was independently associated with higher in-hospital mortality in patients with acute pancreatitis. 30 The study conducted by Zhong et al on critically ill patients with AKI undergoing continuous RRT (CRRT) demonstrated a significant correlation between higher ACAG levels (>20 mmol/L) at the initiation of CRRT and all-cause mortality in the ICU. 18 A recent study has indicated that elevated ACAG levels are associated with an increased risk of all-cause mortality during hospitalization in patients with CA.…”
Section: Discussionmentioning
confidence: 99%
“…If there were multiple measurements of an index within 24 h, the mean value was taken to ensure accuracy. ACAG was calculated using the formula 10 : ACAG (mmol/l) = AG (mmol/l) + [4.4 − albumin (g/dl)] * 2.5, to adjust for the influence of albumin levels. The primary outcome of interest in this study was 30-d mortality in patients diagnosed with asthma.…”
Section: Methodsmentioning
confidence: 99%
“…Although AG is closely related to asthma, the level of AG is greatly affected by the level of albumin 10 , every 1 g/dl decrease in albumin concentration, AG will decrease about 2.5 mmol/L, hypoproteinemia can make AG false negative results. In addition, the use of AG in such patients with abnormal albumin levels is limited because albumin levels are often reduced in patients with asthma 11 .…”
Section: Introductionmentioning
confidence: 99%